Fragments of “insubre identity”: notes regarding the tradition of CIL V, 5216 (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2021)
The Author suggests some reflections about the tradition of a Latin inscription kept in Asso (CO), CIL V, 5216: it is an altar dedicated to a local Genius by two members of the gens Plinia. The comment on this epigraph allows us to highlight the different approach to their own “insubre” past of some scholars of the Renaissance or Counter-Reformation period (Castiglioni, Alciato, Borsieri) compared to that endorsed in a manuscript by Reverend Father Carlo Mazza, the parish priest of Asso between the Eighteenth and Nineteenth centuries.
Keywords: Latin Epigraphy; gens Plinia; Asso; Insubria; Classical tradition; Genius loci